Advances in liver organoids: replicating hepatic complexity for toxicity assessment and disease modeling - Weidong Shao; Hui Xu; Kanghua Zeng; Mingzhou Ye; Renjun Pei; Kai Wang (Stem Cell Research & Therapy)
Abstract The lack of in vivo accurate human liver models hinders the investigation of liver-related diseases, injuries, and drug-related toxicity, posing challenges for both basic research and clinical applications. Traditional cellular and animal models, while widely used, have significant limitations in replicating the liver’s complex responses to various stressors. Liver organoids derived from human pluripotent stem cells, adult stem cells primary cells, or tissues can mimic diverse liver cell types, major physiological functions, and architectural features. Recent advancements in the field have shown that some liver organoids have sufficient accuracy to replicate specific aspects of the human liver’s complexity. This review highlights recent progress in liver organoid research, with a particular emphasis on their potential for toxicity assessment and disease modeling. The intrinsic advantages of liver organoids include higher sensitivity and suitability for long-term studies, which enhance the predictive value in drug and nanomaterial toxicity testing. The integration of liver organoids with microfluidic devices enables the simulation of the liver microenvironment and facilitates high-throughput drug screening. The liver organoids also serve as ideal platforms for studying liver diseases such as hepatitis, liver fibrosis, viral liver diseases, and monogenic diseases. Additionally, this review discusses the advantages and limitations of liver organoids along with potential avenues for future research.